ACUTE ABDOMEN IN A PATIENT WITH COELIAC DISEASE: A CASE REPORT AND LITERATURE REVIEW OF ENTEROPATHY-ASSOCIATED T-CELL LYMPHOMA (EATL). (February 2015) - Jayasinghe, Sureshni I.; Nickless, David
Abstract : A 71-year-old female with a history of poorly-controlled coeliac disease presented with worsening symptoms of small bowel obstruction over 3 weeks. Jejunal, ileal and mesenteric resections were performed. The patient did not recover after surgery and died 3 weeks later. Patchy mucosal ulcerative plaques were seen, corresponding to transmural infiltration by medium-to-large atypical lymphoid cells positive with CD3 and CD56 but negative for CD5, CD8, CD4 and CD20. Similar atypical cells were identified in all regional lymph nodes, in a predominantly sinusoidal distribution. Remaining small bowel mucosa showed typical histological features of coeliac disease, comprising severe villous atrophy, intraepithelial lymphocytosis (reactive lymphocytes) and crypt hyperplasia. EATL of the small intestine with involvement of mesenteric lymph nodes, occurring in the setting of coeliac disease, was diagnosed. EATL is an uncommon lymphoma of intraepithelial T-lymphocytes mostly occurring in patients with coeliac disease. Ten to twenty percent of cases may occur sporadically without coeliac disease (type II EATL) in which monomorphic, medium-sized cells are present. Type II EATL has a distinctive immunophenotype. Both EATL types have very poor prognosis due to low tumour chemosensitivity and aggressive behaviour. Major postsurgical complications are also common in patients who are nutritionally deficient due to coeliac disease.